Studi Diakronis Pronomina Persona Pertama aku dan kami dalam Bahasa Jawa - Fitriana, Atin (Linguistik Indonesia, 2024)
In Old Javanese, the personal pronouns aku and kami can appear simultaneously in a speech and refer to the same person. However, in Modern Javanese first-person pronouns of kami are no longer used in daily conversation; while aku was also limited in the ngoko register. This research focuses on changing the grammatical aspects of the personal pronouns aku and kami diachronically using a grammaticalization and corpus linguistics approach (Mair, 2004; 2012). The data sources used in this research come from literary texts in the form of prose and poetry from the 10th century to the 21st century. In this research, Antconc is used as a data processing tool by utilizing the concordance and frequency row features. Based on frequency, the use of the personal pronouns aku and kami competed with each other from the 10th century to the 18th century. The personal pronouns aku and kami also undergo grammatical development. Bound forms of personal pronouns aku and kami can be attached to nouns, verbs, and prepositions. However, in their development, the bound form can only be attached to nouns. The ability of the bound forms of the pronouns aku and kami to attach to verbs and prepositions is discontinued.